Developing and Sustaining Leaders for Catholic Schools: A Summary of the Conference Proceedings of the Second Catholic Higher Education Collaborative Conference - Boyle, Michael J. (Catholic Education: A Journal of Inquiry and Practice, 2010)
On October 1-3, 2009, Loyola University Chicago’s Center for Catholic School Effectiveness (CCSE) and School of Education hosted the second in a series of six planned Catholic Higher Education Collaborative Conferences (CHEC) entitled, “Developing and Sustaining Leaders for Catholic Schools: How Can Catholic Higher Education Help?” This working conference was structured around four main presentations, each addressing an aspect of the conference theme. Upon the conclusion of each session, conference participants were invited to respond and explore the themes that were presented in each session. This paper provides a summary of the presentations and the discussions of the participants. Finally, the follow-up actions, resulting from the conference, are shared.